KAJIAN COVID-19 PADA PEKERJA DI FASILITAS PELAYANAN KESEHATAN: STUDI 5 PROVINSI TAHUN 2020-2021 - Ma'rifatul Mubin; Robiana Modjo; Riskiyana Sukandhi Putra (Universitas Pahlawan, 2022)
The spread of the SARS-CoV-2 virus is still happening all over the world, including in Indonesia. This situation adds to the already high burden of health services. Health service facilities (fasyankes) are places to control the risk of outbreaks in various special high-risk settings.This study aims to determine the description of COVID-19 occupational diseases in healthcare workers in healthcare facilities in 14 Indonesian Provinces of COVID-19. The increase in COVID-19 cases among health workers is almost evenly distributed in all provinces of the Unitary State of the Republic of Indonesia. This research was conducted in an observational manner with a descriptive approach by collecting data from questionnaires. Questionnaire material comes from the Directorate of Health and Sports, Ministry of Health, Republic of Indonesia. The number of health workers suffering from COVID-19 as proven by standard health checks in 31 health care facilities reached 2,127 cases. The percentage of health workers is 87.26% and non-health workers is 12.74%. The number of health workers who died due to COVID-19 was 14 cases with the percentage of health workers at 92.86% and non-health workers at 7.14%. The number of cases declared as COVID-19 due to work was 137 cases with a percentage of 80.29% for health workers and 19.71% for non-health workers. The number of cases declared COVID-19 due to work is quite high. Health care facilities are one of the workplaces that have the potential to cause transmission due to the very high interaction and mobility of workers. The determination of COVID-19 as an occupational disease has been carried out by 31 health facilities from 5 provinces. Â